The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17145264
|View full text |Cite
|
Sign up to set email alerts
|

Drought, Climate Change, and Dryland Wheat Yield Response: An Econometric Approach

Abstract: Agriculture has been identified as one of the most vulnerable sectors affected by climate change. In the present study, we investigate the impact of climatic change on dryland wheat yield in the northwest of Iran for the future time horizon of 2041–2070. The Just and Pope production function is applied to assess the impact of climate change on dryland wheat yield and yield risk for the period of 1991–2016. The Statistical Downscaling Model (SDSM) is used to generate climate parameters from General Circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…is the 10th most commonly cultivated cereal worldwide and one of the most important food crops in the Mediterranean Rim with an important role in the human diet [1,2]. However, its production is threatened by climate change and extreme weather events [3][4][5]: North Africa, including Tunisia, is recognized as a climate change hotspot region [6][7][8] and is, therefore, particularly vulnerable to drought stress [9][10][11][12][13], which limits growth, development, and crop yield [14][15][16][17]. By 2030, Tunisia is expected to suffer from an annual average increase in temperature of 1.1 • C and thus an annual acute decrease in precipitation and water resources [6].…”
Section: Introductionmentioning
confidence: 99%
“…is the 10th most commonly cultivated cereal worldwide and one of the most important food crops in the Mediterranean Rim with an important role in the human diet [1,2]. However, its production is threatened by climate change and extreme weather events [3][4][5]: North Africa, including Tunisia, is recognized as a climate change hotspot region [6][7][8] and is, therefore, particularly vulnerable to drought stress [9][10][11][12][13], which limits growth, development, and crop yield [14][15][16][17]. By 2030, Tunisia is expected to suffer from an annual average increase in temperature of 1.1 • C and thus an annual acute decrease in precipitation and water resources [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the Cobb-Douglas Yield Response (CDYR) model was used to assess the sensitivity of crops yield to climatic variables, such as minimum and maximum temperatures, as well as precipitation [47,48]. The CDYR model, after taking the logarithm of both sides of the equation, can be presented as follows:…”
Section: Economic Models 251 Generalized Maximum Entropy (Gme) Modelmentioning
confidence: 99%
“…This study found that the quantity of labor and amount of chemicals applied had statistical significance and positively correlated with sugarcane production. In recent studies of Guntukula and Goyari (2020), Pipitpukdee et al (2020), Sarkar et al (2020), andShayanmehr et al (2020) focused on the impact of climatic and non-climatic factors on the productivity of agricultural commodities using the panel data analysis. The findings from these empirical studies confirmed that climatic factors could be one of the most important factors in the efficiency of agricultural production.…”
Section: Literature Reviewmentioning
confidence: 99%